DEVELOVING CHARACTER EDUCATION WITH REFERENCE TO ISLAMIC PERSPECTIVE: A CONCEPTUAL REVIEW - Supriyono Supriyono (JARES (Journal of Academic Research and Sciences), 2016)
The paper focuses on the description of how character education is effectively developed and implemented. Using qualitative descriptive method, the writer presents efforts for character education in various countries and synrthesizes to formulate a proposed effective character education system. Character education in Indonesia has been the priority and the implentation is mandated to be included in all subject matters through curriculair and extra-curriculair activities. Effective practical implementation must be taken care off. The suggestive development and implementation of the character education include the strenghtenning of being valued people as in ikhsan, being good creatures of Allah as in Iman, and being able to do good deeds and moral action in the community as in Islam. These can be done through academic lessons, habituations, creativity-action and services. Character development is suggested to be internalized in the wholistic education system by developing the whole students ’ potential through various active learnings and habituation.